Calidad de vida de los pacientes con enfermedad pulmonar obstructiva crónica y su participación en programas de rehabilitación respiratoria, en el Hospital General Martin Icaza, Babahoyo Los Ríos, segundo semestre 2019 - Figueroa Bohórquez, Lady Diana (2019)
There is a serious problem in the world population caused by Chronic Obstructive Pulmonary Disease characterized by airway obstruction due to chronic bronchitis and pulmonary emphysema, one of the main risk factors is cigarette smoking. Patients who arrive at health centers indicate that they began their consumption at an early age, it is estimated that this chronic disease in the next ten years will be the third leading cause of death worldwide. The objective is to demonstrate that the respiratory rehabilitation program is an effective procedure to be able to improve the quality of life of patients with COPD, so that they can continue with their daily activities in a better way. This project is based on a field study, using methods with a qualitative and quantitative approach. The results that have been obtained have been through surveys, resulting in many patients not having adequate respiratory rehabilitation because their quality of life is diminished, this being analyzed by questionnaires that measure the quality of life as So are the Saint George Respiratory Questionnaire and the Chronic Respiratory Disease Questionnaire.